Legal and social issues in the development of waste management in Malaysia - Gamon, Alizaman Dumangcag; Tagaranao, Mariam Saidona (Innovative Research Publications, 2016)
Throughout man’s history, waste disposal has put great stress in maintaining a clean and healthy green environment. The tremendous increasing amount of solid waste becomes a major challenge for the people and the government in analyzing the national legislations and the international policy framework for an effective control and enforcement measures in handling the waste management. Failure of a state to implement the effective rules, regulations and social policies will lead to numerous environmental hazards. The objective of this paper is to analyze the national legislations and policies in developing the methods necessary to formulate waste management plans in Malaysia. The Solid Waste and Public Cleaning Management (Act 672) came into effect in 2011 and then proceeded by awareness programs to educate people on the 3R concept – reduce, reuse and recycle. This paper attempts to discuss some practical methods introduced by the government, like the so-called “waste-separation scheme” which was implemented in September 2012. This scheme is in accordance with the government declaration of educating the people about going green. At the end, we make some recommendations in reducing the current negative social impact of environmental changes due to an increasing quantity of waste disposal.